An applied Mobile Truck Model (MTM) for on-the-road data-probing. (17th October 2011) - Morgan, Y.; Kunz, T.
In recent years, the blending of wireless technologies with modern safety features allows to deliver safer, faster and potentially greener vehicles. In this paper, we present a model based on heavy vehicles into the area of data probing, called Mobile Truck Model (MTM). The model benefits from heavy trucks as a data-probing vehicle by benefiting from its relative elevation over other vehicles. The result is better economics for operated heavy trucks. We illustrate how to limit disruption to communications, and we present alternative foundation models that can be combined with our proposal and discuss how they affect its validity and performance.